Equilibrium and muscle flexibility in elderly people subjected to physiotherapeutic intervention - Mariane Fernandes Ribeiro; Lislei Jorge Patrizzi; Vicente de Paula Antunes Teixeira; Ana Paula Espindula (Universidade Estadual de Maringá, 2016)
To evaluate the equilibrium and flexibility of elderly people submitted to a training program involving physical therapy exercises. Six elderly people were selected, average age 69.66 years. Wells's Bench and the Functional Reach Test (FRT) plus Timed Up and Go Test (TUG) were employed respectively to assess muscle flexibility and balance analysis. Tests were performed before and after the exercise program which consisted of thirty-five 50 min physical therapy group sessions, twice a week, with stretching exercises, gait training, active exercises, postural correction exercises and breathing exercises. Statistical analysis was done with Sigma-Stat® 3.5. Assessments occurred before and after sessions, and the final test was undertaken after 35 sessions. There was a statistically significant increase in the flexibility of the posterior muscle chain. In the TUG test, the group achieved a shorter time after treatment, with statistical significance between tests. There was a statistically significant increase in the average FRT after the sessions. Current study showed better results in the execution of tests evaluated after the program of physiotherapy activities, contributing towards the improvement of muscle flexibility and balance of elderly people.